PENGEMBANGAN BAHAN AJAR FISIKA MENGINTEGRASIKAN NILAI-NILAI KARAKTER PADA MATERI HUKUM NEWTON UNTUK PEMBELAJARAN PESERTA DIDIK KELAS X SMAN 9 P0NTIANAK - Tursina Tursina; Haratua Tiur Maria Silitonga; Erwina Oktavianty (Universitas Tanjungpura, 2021)
AbstractThis research aims to produce teaching material product that integrates character values as appropriate teaching material and to know the students’ and teacher’s responses toward the developed product. The design of research used is the ADDIE model. The teaching material was tried out to the tenth-grade students of MIA 2 in SMAN 9 Pontianak. To collect the data, the instruments used were eligibility questionnaire, students’ response questionnaire, and teacher’s response questionnaire. The data results show that the learning material integrating character values that being developed has valid eligibility level on appropriate material/content (79,4%), very valid on presentation eligibility (93,3%), very valid on character eligibility (90%), valid on language eligibility (73,3%), and valid on graphics eligibility (81,5%). The result of students try out responses score on the product was 81,8%, which is classified very high and the teacher response try out score was 77,2% which is classified high. Hence, teaching materials integrating character values as teaching materials are appropriate for use in the learning process. This research is expected to be used by teachers as an alternative media for teaching.Keywords: Teaching material, character, eligibility, students response, teacher response